Predictors of major depression in recently diagnosed patients with HIV/AIDS in South Africa (2004)
There is increasing evidence that major depression impacts the course of HIV infection, yet few studies have explored demographic and clinical predictors of depression in people who with HIV/AIDS. This study investigated predictors of depression (e.g., demographic and clinical variables, negative life events, and coping response) among outpatients with recently diagnosed HIV/AIDS patients in South Africa. One hundred forty-nine recently diagnosed HIV/AIDS patients (44 males and 105 females; mean time since diagnosis= 5.8, standard deviation [SD] 4.1) were evaluated. Subjects were assessed using the Mini International Neuropsychiatric Interview (MINI), the Carver Brief COPE coping scale, and the Sheehan Disability Scale. In addition, previous exposures to trauma and past risk behaviors were assessed. Three variables: gender (odd ratio [OR]= 1.23; 95% confidence interval [CI] 1.56, 1.93), impact of negative life events (OR= 1.13; CI, 1.03, 1.23), and disability (OR= 1.51, CI, 1.28, 1.80) predicted current major depression. It is well known from non-HIV populations that female gender and increased negative life events predict depression. These data also emphasize the importance of these links in HIV.